2015
DOI: 10.1080/02648725.2015.1020467
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological interventions inWithania somnifera(L.) Dunal

Abstract: Withania somnifera is one of the most valued plants and is extensively used in Indian, Unani, and African systems of traditional medicine. It possess a wide array of therapeutic properties including anti-arthritic, anti-aging, anti-cancer, anti-inflammatory, immunoregulatory, chemoprotective, cardioprotective, and recovery from neurodegenerative disorders. With the growing realization of benefits and associated challenges in the improvement of W. somnifera, studies on exploration of genetic and chemotypic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 83 publications
(95 reference statements)
1
24
0
Order By: Relevance
“…Withania somnifera (Solanaceae family), commonly called Ashwagandha or Indian ginseng, is an important medicinal shrub that grows to about a meter in height on slightly basic and moist soil at optimal temperatures of 20–32°C. Extensively used in Indian, Unani and African traditional medicines, it has been categorized in GRAS (Generally Regarded As Safe) food substances by WHO [13]. Ashwagandha is well known for its enormous therapeutic potential for a large number of ailments, including stress, cardiac, brain and immune disorders, inflammation and cancer [2, 411].…”
Section: Introductionmentioning
confidence: 99%
“…Withania somnifera (Solanaceae family), commonly called Ashwagandha or Indian ginseng, is an important medicinal shrub that grows to about a meter in height on slightly basic and moist soil at optimal temperatures of 20–32°C. Extensively used in Indian, Unani and African traditional medicines, it has been categorized in GRAS (Generally Regarded As Safe) food substances by WHO [13]. Ashwagandha is well known for its enormous therapeutic potential for a large number of ailments, including stress, cardiac, brain and immune disorders, inflammation and cancer [2, 411].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report it was suggested that shoots cultured in half-strength MS liquid medium amended with BAP (5.0  µ M) accumulated higher biomass and withaferin A (1.5-fold) within 5 weeks of culture [65]. The enhanced accumulation of biomass and withaferin A due to BAP may attribute to its property to induce shoot proliferation [66], as withaferin A is present majorly in the leaves [1]. It was also observed that various glycowithanolides (Physagulin D, Withastraronolide, Withanoside IV, and Withanoside VI) accumulate in shoots cultured in BAP (4.44  µ M) [67].…”
Section: Modulation Of Secondary Metabolites Using In Vitro Culturmentioning
confidence: 99%
“…Withania somnifera (L.) Dunal (family Solanaceae) holds high repute in Indian, Greek, and African traditional system of medicine [1]. It is commonly referred to as Ashwagandha, Asgandh, Winter cherry, or Indian ginseng.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations